Utilization of the MOORA Method for Recommended Selection of Best Waiters in Hospitality - Preddy Marpaung; Henri Pandiangan (IJISTECH (International Journal of Information System and Technology), 2020)
Hospitality waiters are the spearhead in a hotel's service with a variety of tasks ranging from food preparation, room arrangement, serving guests, and other tasks. So waiters as hotel employees are very influential on the quality of service to consumers. To motivate waiters to provide better service to consumers, a decision-making system is needed in selecting the best waiters according to the criteria determined by management. With the creation of the best waitress selection system to get an award according to the specified criteria, waiters will compete to provide the best service to impact hospitality positively. The method used in selecting the best waiters at The K Hotel Medan by utilizing the MOORA method, using the MOORA method can produce good and effective decisions in recommending the best waiters according to the highest value, namely rank 1, so that with a decision support system using the MOORA method This can help hotel management determine their best waiters for each episode objectively.